Anastomotic Leak Does Not Impact Oncologic Outcomes After Preoperative Chemoradiotherapy and Resection for Rectal Cancer. Issue 4 (April 2019) - Jang, Jae Hyuck; Kim, Hee Cheol; Huh, Jung Wook; Park, Yoon Ah; Cho, Yong Beom; Yun, Seong Hyeon; Lee, Woo Yong; Yu, Jeong Il; Park, Hee Chul; Park, Young Suk; Park, Joon Oh
Abstract : Objective: The aim of this study was to evaluate the relationship of anastomotic leakage, local recurrence, and overall survival in rectal cancer patients treated with preoperative chemoradiotherapy (CRT) and curative resection. Background: Little is known about the association between anastomotic leakage and oncologic outcomes after preoperative CRT. Methods: A total of 698 consecutive primary rectal cancer patients after preoperative CRT between April 19, 2000, and December 27, 2013, were retrospectively reviewed. Forty-seven patients who had anastomotic leakage were compared with 651 patients who had no anastomotic leakage. Results: Of 698 patients, 47 (6.7%) patients had anastomotic leakage. Among these 47 patients, 39 (83.0%) had grade C leak that required urgent operation, while 8 (17.0%) had grade B leak that was managed expectantly or by percutaneous drainage. The median follow-up period was 47.6 months (range, 27.1 to 68.9 months). One hundred twenty (17.2%) recurrences were identified among all patients. The median overall disease-free survival was 43 months (range, 22.4 to 66.7 months). Five-year disease-free survival did not differ significantly between the 2 groups (80.5% vs 80.4%, P = 0.839). Five-year local recurrence-free survival did not differ significantly either between the 2 groups (93.7% vs 94.9%, P = 0.653). Five-year overall survival rates of patients with or without leakage were 90.9% and 86.3%, respectively ( P = 0.242). Five-year cancer-specific survival rates of patients with or without leakage were 92.2% and 86.3%, respectively ( P = 0.248). Conclusion: After preoperative CRT, an anastomotic leak is not associated with a significant increase in local recurrence or long-term survival in rectal cancer.